Case report: Shingles-associated probable Bickerstaff brainstem encephalitis with IgM anti-sulfatide positivity - Fu, Xiaoxue; Zhan, Qianli; Zhang, Linjie; Tian, Xiaoyan (Frontiers in Immunology, 2024)
Background: Bickerstaff brainstem encephalitis (BBE) is a rare disease considered to be due to acute demyelination of the brainstem, most often resulting from secondary autoimmune responses. To our knowledge, this is the first probable case report of shingles-associated BBE with anti-sulfatide IgM positivity.Case presentation: We report the case of an 83-year-old woman with symptoms of progressive limb weakness, difficulty swallowing food and disturbed consciousness which occurred 4 weeks following Herpes zoster infection. In our case, autoimmune anti-sulfatide antibodies were positive and Fluid attenuated inversion recovery (FLAIR) sequences revealed clear high signal intensity in pons and bilateral thalamus. Our patient's condition improved markedly with glucocorticoid treatment. After 2 months of treatment, our patient was fully recovered. We considered that BBE provided the most appropriate diagnose.The importance of a careful medical history and assessment of clinical symptoms, performing MRI and testing autoimmune antibodies and for rapid diagnosis and ruling out differential diagnoses is emphasized. Further studies involving more patients with BBE with IgM anti-sulfatide autoantibodies will increase understanding of the clinical characteristics and advance diagnosis and treatment of this syndrome. Meanwhile, it is crucial for dermatologists to know about this severe neurological complication following shingles.